Faktor yang Berhubungan dengan Penerapan 6 Sasaran Keselamatan Pasien - Miko Eka Putri; Fithriyani Fithriyani; Mila Triana Sari (Universitas Baiturrahim, 2022)
Patient safety is a system that must be implemented in hospitals. This is done by the government in an effort to prevent patient safety incidents from occurring. Based on the Lumenta report (2008) that in Indonesia from 145 reported incidents of near-injury (KNC) as many as 47.6% cases, unwanted events (KTD) as many as 46.2% cases, and others as many as 6.2% cases. . The KTD rate at Raden Mattaher Hospital in 2016 was 10 cases, increasing to 13 cases in 2017 and decreasing to 7 cases in 2018. Many factors affect the implementation of patient safety, namely internal and external factors. The purpose of this study was to determine the factors associated with the implementation of 6 patient safety goals at Raden Mattaher Hospital Jambi. The design of this study used a cross-sectional study. The number of samples in this study were 80 nurses with proportional random sampling technique. The analysis used was univariate and bivariate analysis with Chi-square and Wilcoxon tests. The results of the analysis show that the average age is 33.19 years and the length of work is 9.39 years. A total of 71.2% are female, 82.5% have vocational education, 68.8% have sufficient knowledge, 56.2% are positive and 65% of respondents do not apply the 6 patient safety goals. The results of the bivariate analysis showed that there was a relationship between age, length of work and attitude with the implementation of the 6 patient safety goals.